STRATEGI PEMASARAN PADA UMKM BATU BATA DI KALORAN KECAMATAN NGRONGGOT - Azuhri, Mohamad Baitul Ulum Dwi; Ernestivita, Gesty; Sasongko, M. Zuhdi (Universitas Nusantara PGRI Kediri, 2023)
This study aims to analyze the marketing strategy of brick SMEs in Kaloran, Ngronggot District. Data obtained from the owner, and employees. The research method used is a qualitative method. The results of the marketing strategy research implemented by Batu Bata MSMEs in Kaloran Village are quite common and fairly traditional, therefore there is a need for developments in terms of the MSME marketing strategy and the effectiveness of marketing planning at Batu Bata MSMEs in Kaloran, Ngronggot District, sales targets namely consumers who have activities or the task of building a building requires bricks, the owner has prepared a monthly and annual basic budget so the budget design for the UMKM Bricks in Kaloran Village is quite good, and prioritizes the quality of its products even though the price is different from its competitors.